CNTs reinforced asphalt pervious concrete and preparation method thereof
By adding CNTs reinforcement materials to asphalt permeable concrete, combined with the stirring and mixing of modified asphalt and aggregate, the problem of low mechanical properties of asphalt permeable concrete in the prior art is solved, and the permeability and structural mechanical properties of asphalt permeable concrete are realized. Overall improvement.
Patent Information
- Application Number
- CN202411583149.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-14
AI Technical Summary
While improving water permeable concrete materials, the existing asphalt permeable concrete materials have low mechanical properties, resulting in the problems of falling off the surface aggregate, low strength and poor durability.
By adding CNTs reinforcement materials to asphalt permeable concrete, combining the stirring and mixing of modified asphalt and aggregates, the bonding performance of aggregates is improved, and the crack resistance and bearing capacity of the material is enhanced through the physical properties of CNTs, and the pore distribution and formation network are optimized. .
It significantly improves the mechanical properties and durability of asphalt permeable concrete, improves the overall level of water permeability and structural mechanical properties, and extends the service life of the road surface.
Smart Images

Figure BDA0005123650100000071 
Figure BDA0005123650100000072 
Figure BDA0005123650100000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of asphalt concrete road materials, and in particular to CNTs reinforced asphalt permeable concrete and a preparation method thereof. Background Art
[0002] my country's highway traffic is in a rapid development stage. At present, domestic highway pavement is mainly made of impermeable asphalt mixture and concrete. However, this dense surface pavement has poor drainage performance. Under the combined effects of water immersion erosion and traffic load, it is easy to cause problems such as cracking of the original pavement, reducing the service life of the asphalt pavement. In addition, the reduction of rainwater infiltration will affect the ecological balance of the city and cause the urban "heat island effect".
[0003] Asphalt permeable concrete material has great advantages in the development of green environmental protection. It is made of coarse and fine aggregates, powdered fillers, and matrix asphalt as the main raw materials. The porosity of its pavement structure is relatively high, which can make the water on the road surface quickly seep out and effectively avoid the appearance of pavement water drift and upper water film. At the same time, its road surface roughness is relatively large, and it has the function of anti-skid and noise reduction, which improves the safety and comfort of driving. However, at present, the asphalt permeable concrete surface layer aggregate falls off, the strength is low, and the durability is poor due to factors such as the large porosity of the asphalt permeable material itself, the insignificant pressure bearing and deformation resistance. For example, the Chinese invention patent with the publication number CN112897959B discloses a permeable high-strength asphalt concrete and its preparation method, optimizes the mix ratio of the permeable asphalt mixture, and increases its porosity and pore size by adjusting the skeleton structure of the asphalt aggregate, so as to achieve the effect of improving the permeability of the asphalt pavement. Although this method improves the permeability to a certain extent, it also reduces the compressive strength of the skeleton structure and weakens the bonding effect of the slurry between aggregates, which in turn increases the occurrence of problems such as damage to asphalt permeable pavement.
[0004] In view of this, it is necessary to innovate and improve asphalt permeable concrete materials, and enhance their mechanical properties while ensuring their high permeability coefficient. Summary of the invention
[0005] The purpose of the present invention is to provide a CNTs-enhanced asphalt permeable concrete and a preparation method thereof, wherein the viscosity of the modified asphalt and the thickness of the asphalt coating on the aggregate surface are increased by absorbing the light component after the reinforcing material CNTs is stirred and mixed with the modified asphalt, and the bonding performance of the aggregate is further improved; at the same time, the excellent physical properties of the reinforcing material CNTs are utilized to not only enhance the crack resistance and bearing capacity of the asphalt permeable concrete, but also improve the durability of the asphalt permeable concrete, and the reinforcing material CNTs particles with a reasonable dosage can optimize the pore distribution of the asphalt mixture, form a network cross-linking system, reduce the pore blockage of the permeable asphalt concrete, thereby achieving an overall improvement in the permeability and structural mechanical properties of the asphalt pavement. The present invention well solves the technical problems of the current low performance and poor durability of the materials used in the asphalt permeable concrete pavement, thereby better meeting the functional requirements of the pavement.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] In the first aspect, the present invention provides a CNTs-reinforced asphalt permeable concrete, which is composed of the following components in parts by weight: 4 to 12 parts of modified asphalt, 75 to 85 parts of coarse aggregate, 6 to 10 parts of fine aggregate, 4 to 7 parts of cement, 3 to 5 parts of mineral powder, 1 to 1.5 parts of slaked lime, and 0.2 to 0.8 parts of reinforcing material CNTs.
[0008] As a specific technical solution of the present invention, CNTs-enhanced asphalt permeable concrete is composed of the following components in parts by weight: 5.2 parts of modified asphalt, 78.5 parts of coarse aggregate, 7.1 parts of fine aggregate, 4.6 parts of cement, 3 parts of mineral powder, 1.4 parts of slaked lime, and 0.2 parts of reinforcing material CNTs.
[0009] As a specific technical solution of the present invention, CNTs-enhanced asphalt permeable concrete is composed of the following components in parts by weight: 5.5 parts of modified asphalt, 76.4 parts of coarse aggregate, 7.6 parts of fine aggregate, 5 parts of cement, 3.7 parts of mineral powder, 1.5 parts of slaked lime, and 0.3 parts of reinforcing material CNTs.
[0010] As a specific technical solution of the present invention, CNTs-enhanced asphalt permeable concrete is composed of the following components in parts by weight: 4.5 parts of modified asphalt, 80.2 parts of coarse aggregate, 6.2 parts of fine aggregate, 4.1 parts of cement, 3.2 parts of mineral powder, 1.5 parts of slaked lime, and 0.3 parts of reinforcing material CNTs.
[0011] Furthermore, the modified asphalt is mixed with base asphalt, a modifier and a composite stabilizer, the dosage of the modifier is 4.5% to 5.5%, and the dosage of the composite stabilizer is 0.1% to 0.2%.
[0012] Furthermore, the modifier is prepared by copolymerization of petroleum resin, styrene and modified high-performance polyurethane resin in a mass ratio of 100:7-9:10-14.
[0013] Preferably, the mass ratio of petroleum resin, styrene and modified high-performance polyurethane resin is 100:7:11.
[0014] Furthermore, the composite stabilizer is composed of sulfur powder, polyvinyl alcohol and toluene diisocyanate in a mass ratio of 100:20-30:5-10.
[0015] Preferably, the mass ratio of sulfur powder, polyvinyl alcohol and toluene diisocyanate is 100:22:8.
[0016] Furthermore, the coarse aggregate is a hard stone mixed with basalt, diabase and limestone, the particle size range of the coarse aggregate is 3.0mm~15.0mm, and the specific grading range is: the pass rate of the sieve hole size of 16mm is 100%, the pass rate of the sieve hole size of 13.2mm is 85%~87%, the pass rate of the sieve hole size of 9.5mm is 30%~32%, the pass rate of the sieve hole size of 4.75mm is 5.0%~6.4%, and the pass rate of the sieve hole size of 2.36mm is 0.5%~1.0%.
[0017] Furthermore, the fine aggregate is limestone, and the particle size range of the fine aggregate is 0.075mm~3.0mm. The specific grading range is: the pass rate of the sieve hole size of 4.75mm is 100%, the pass rate of the sieve hole size of 2.36mm is 90%~92%, the pass rate of the sieve hole size of 1.18mm is 64%~66%, the pass rate of the sieve hole size of 0.6mm is 52%~54%, the pass rate of the sieve hole size of 0.3mm is 25%~26%, the pass rate of the sieve hole size of 0.15mm is 18%~18.5%, and the pass rate of the sieve hole size of 0.075mm is 3.2%~3.6%.
[0018] Furthermore, the cement is ordinary Portland cement, and its 28-day compressive strength is ≥42.5MPa, 28-day flexural strength is ≥7.0MPa, and specific surface area is ≥320m 2 / kg.
[0019] Furthermore, the mineral powder is limestone mineral powder, the particle size range is ≤0.075 mm, the 28-day activity index is ≥95%, and the specific surface area is ≥420 m 2 / kg.
[0020] Furthermore, the slaked lime is a white powder matrix with an apparent density of ≥2.2 g / cm 3 .
[0021] Furthermore, the reinforcing material CNTs is a multi-walled hydroxy carbon nanotube with a diameter of 10nm to 20nm, a length of 30μm to 50μm, and a specific surface area of ≥220m 2 / g.
[0022] In a second aspect, the present invention also provides a method for preparing the above-mentioned CNTs-enhanced asphalt permeable concrete, comprising the following steps:
[0023] S1. Preheat the stirring device to 155℃~165℃, add graded coarse aggregate and fine aggregate into the stirring device, and stir and mix evenly for 100s~150s;
[0024] S2, heating the modified asphalt to 165° C., adding it to the aggregate treated in step S1, continuing to stir for 180s to 200s, then adding cement, mineral powder and slaked lime, and mixing for 120s to 180s in a stirring manner to obtain an asphalt mixture;
[0025] S3, adding the reinforcing material CNTs to the asphalt mixture of step S2, heating to 180°C to 200°C, and performing high-speed shear stirring at a speed of 3000r / min to 3200r / min for 60s to 120s to obtain CNTs-reinforced asphalt permeable concrete.
[0026] Compared with the prior art, the present invention provides a CNTs-reinforced asphalt permeable concrete and a preparation method thereof, which has the following beneficial effects:
[0027] (1) The present invention uses CNTs as a reinforcing material to significantly improve the mechanical properties of asphalt permeable concrete while maintaining its permeability. Specifically, by mixing CNTs with modified asphalt, the compatibility between internal particles is improved, the lightweight components are fully absorbed, the viscosity of the modified asphalt is enhanced in the multi-void structure, and the thickness of the asphalt coating on the aggregate surface is increased, thereby greatly improving the bonding performance and high-temperature elastic recovery performance of the material. The filler of the present invention is composed of cement, mineral powder and slaked lime. Using slaked lime to replace part of the cement and mineral powder can further improve the interface adhesion between asphalt and aggregate.
[0028] (2) Compared with the traditional asphalt permeable pavement, the present invention adds the reinforcing material CNTs to the asphalt permeable concrete, which not only has the advantages of good pavement anti-rutting ability, high bearing strength and strong anti-aging performance, but also can reduce the bending stiffness modulus of the mixture, enhance its toughness, and significantly enhance the crack resistance and deformation capacity. At the same time, the CNTs particles with a reasonable amount can optimize the pore distribution of the asphalt mixture, form a stable network cross-linking system, reduce the pore blockage of the permeable asphalt concrete, enhance the durability and water stability of the asphalt permeable concrete, and thus achieve the overall improvement of the permeability and structural mechanical properties of the asphalt pavement. DETAILED DESCRIPTION
[0029] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In the examples and comparative examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0031] The present invention is further described in detail below through detailed examples.
[0032] Example 1
[0033] The present embodiment provides a CNTs-reinforced asphalt permeable concrete, which is composed of the following components in parts by weight: 5.2 parts of modified asphalt, 78.5 parts of coarse aggregate, 7.1 parts of fine aggregate, 4.6 parts of cement, 3.0 parts of mineral powder, 1.4 parts of slaked lime, and 0.2 parts of reinforcing material CNTs.
[0034] Among them, the modified asphalt is made by mixing the base asphalt with the modifier and the composite stabilizer under high temperature shearing, with the modifier content being 4.8% and the composite stabilizer content being 0.12%. The modifier is made by copolymerization of petroleum resin, styrene and modified high-performance polyurethane resin in a mass ratio of 100:7:11. The composite stabilizer is composed of sulfur powder, polyvinyl alcohol and toluene diisocyanate in a mass ratio of 100:22:8.
[0035] The coarse aggregate is a hard stone mixed with basalt, diabase and limestone. The particle size range of the coarse aggregate is 3.0mm to 15.0mm. The specific grading range is shown in Table 1 below.
[0036] Table 1 Grading record of coarse aggregate in Example 1
[0037]
[0038] The fine aggregate is limestone, and the particle size range of the fine aggregate is 0.075mm to 3.0mm. The specific grading range is shown in Table 2 below.
[0039] Table 2 Grading record of fine aggregate in Example 1
[0040]
[0041] The cement is ordinary Portland cement, with a 28-day compressive strength of ≥42.5MPa, a 28-day flexural strength of ≥7.0MPa, and a specific surface area of ≥320m2 / kg.
[0042] The mineral powder is limestone mineral powder with a particle size range of ≤0.075mm, a 28-day activity index of ≥95%, and a specific surface area of ≥420m 2 / kg.
[0043] Slaked lime is a white powder matrix with an apparent density of ≥2.2g / cm 3 .
[0044] The reinforcing material CNTs is a multi-walled hydroxy carbon nanotube with a diameter of 12nm, a length of 30μm, and a specific surface area of 270m 2 / g.
[0045] The preparation method of the CNTs-reinforced asphalt permeable concrete comprises the following steps:
[0046] S1. Preheat the stirring device to 165°C, add graded coarse aggregate and fine aggregate into the stirring device according to the mass proportion of the formula, and stir and mix evenly for 120 seconds;
[0047] S2. Heat the modified asphalt to 165° C. according to the mass fraction of the formula, add it to the aggregate treated in step S1, continue stirring for 180 seconds, then add the corresponding mass fractions of cement, mineral powder and slaked lime, mix for 150 seconds while adding and stirring, to obtain an asphalt mixture;
[0048] S3. Add the reinforcing material CNTs to the asphalt mixture of step S2 according to the mass fraction of the formula, heat to 200° C., and perform high-speed shear stirring at a speed of 3000 r / min for 90 seconds to obtain CNTs-reinforced asphalt permeable concrete.
[0049] Example 2
[0050] The present embodiment provides a CNTs-reinforced asphalt permeable concrete, which is composed of the following components in parts by weight: 5.5 parts of modified asphalt, 76.4 parts of coarse aggregate, 7.6 parts of fine aggregate, 5.0 parts of cement, 3.7 parts of mineral powder, 1.5 parts of slaked lime, and 0.3 parts of reinforcing material CNTs.
[0051] Among them, the modified asphalt is made by mixing the base asphalt with the modifier and the composite stabilizer under high temperature shearing, with the modifier content being 4.9% and the composite stabilizer content being 0.1%. The modifier is made by copolymerization of petroleum resin, styrene and modified high-performance polyurethane resin in a mass ratio of 100:7:11. The composite stabilizer is composed of sulfur powder, polyvinyl alcohol and toluene diisocyanate in a mass ratio of 100:22:8.
[0052] The coarse aggregate is a hard stone mixed with basalt, diabase and limestone. The particle size range of the coarse aggregate is 3.0mm~15.0mm. The specific grading range is shown in Table 3 below.
[0053] Table 3 Grading record of coarse aggregate in Example 2
[0054]
[0055] The fine aggregate is limestone, and the particle size range of the fine aggregate is 0.075mm to 3.0mm. The specific grading range is shown in Table 4 below.
[0056] Table 4 Grading record of fine aggregate in Example 2
[0057]
[0058] The specific settings of cement, mineral powder, slaked lime and reinforcing material CNTs used in this embodiment are the same as those in Example 1. At the same time, the preparation method of CNTs-reinforced asphalt permeable concrete provided in this embodiment is also the same as that in Example 1, so it will not be repeated here.
[0059] Example 3
[0060] The present embodiment provides a CNTs-reinforced asphalt permeable concrete, which is composed of the following components in parts by weight: 4.5 parts of modified asphalt, 80.2 parts of coarse aggregate, 6.2 parts of fine aggregate, 4.1 parts of cement, 3.2 parts of mineral powder, 1.5 parts of slaked lime, and 0.3 parts of reinforcing material CNTs.
[0061] Among them, the modified asphalt is made by mixing the base asphalt with the modifier and the composite stabilizer under high temperature shearing, with the modifier content being 4.7% and the composite stabilizer content being 0.15%. The modifier is made by copolymerization of petroleum resin, styrene and modified high-performance polyurethane resin in a mass ratio of 100:7:11. The composite stabilizer is composed of sulfur powder, polyvinyl alcohol and toluene diisocyanate in a mass ratio of 100:22:8.
[0062] The coarse aggregate is a hard stone mixed with basalt, diabase and limestone. The particle size range of the coarse aggregate is 3.0mm~15.0mm. The specific grading range is shown in Table 5 below.
[0063] Table 5 Grading record of coarse aggregate in Example 3
[0064]
[0065] The fine aggregate is limestone, and the particle size range of the fine aggregate is 0.075mm~3.0mm. The specific grading range is shown in Table 6 below.
[0066] Table 6 Grading record of fine aggregate in Example 3
[0067]
[0068] The specific settings of cement, mineral powder, slaked lime and reinforcing material CNTs used in this embodiment are the same as those in Example 1. At the same time, the preparation method of CNTs-reinforced asphalt permeable concrete provided in this embodiment is also the same as that in Example 1, so it will not be repeated here.
[0069] Comparative Example 1
[0070] This comparative example is set up based on Example 1. The difference from Example 1 is that the reinforcing material CNTs is replaced with the same mass fraction and the density is 1.3g / cm 3 The ground rubber powder and other settings are the same as those in Example 1 to prepare asphalt permeable concrete.
[0071] Comparative Example 2
[0072] This comparative example is set up based on Example 2. The difference from Example 2 is that this comparative example does not contain slaked lime (replaced by limestone mineral powder), the filler is cement powder and ground limestone mineral powder, and the rest of the settings are the same as Example 2 to obtain asphalt permeable concrete.
[0073] Experimental testing
[0074] Marshall test pieces were prepared using the asphalt concretes prepared in Examples 1 to 3 and Comparative Examples 1 to 2, respectively, and the two sides of the molded test pieces were struck 50 times each.
[0075] The connected porosity and water permeability coefficient of the asphalt concrete Marshall specimens prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were tested by the constant water head method, and their average values were compared. At the same time, the asphalt softening point test ring and ball method was used to test the asphalt softening point, and the test results were recorded as shown in Table 7 below.
[0076] Table 7 Test result record
[0077]
[0078] From the experimental data in Table 7, it can be seen that in the present invention, the asphalt permeable concrete prepared by adding the reinforcing material CNTs has higher Marshall stability, porosity, water permeability coefficient and rutting dynamic stability, the softening point of asphalt tends to be stable, and the reinforcing material CNTs has a positive effect on the overall performance of asphalt permeable concrete. Comparison of Example 1 and Comparative Example 1 shows that Example 1 can improve the compatibility between internal particles by adding the reinforcing material CNTs, thereby improving the structural strength of asphalt, further improving the anti-rutting performance and toughness of asphalt permeable concrete, avoiding the damage of the road surface after long-term vehicle heavy-load rolling, and effectively extending the durability and service life of the road surface.
[0079] By comparing Example 2 with Comparative Example 2, it can be seen that since no slaked lime is added in Comparative Example 2, while Example 2 uses slaked lime as a filler to add to the modified asphalt, the bonding ability of the asphalt permeable concrete in Comparative Example 2 is poor, and its Marshall stability and water permeability coefficient are poor. Since slaked lime is used to replace part of the mineral powder, the interface adhesion between asphalt and aggregate can be improved, and together with the reinforcing material CNTs, the bonding performance of the asphalt permeable concrete prepared in Example 2 can be significantly improved, not only enhancing the Marshall stability and rutting dynamic stability, but also enabling the asphalt pavement to maintain a high porosity and water permeability coefficient.
[0080] The above embodiments are merely illustrative of the concept and technical solution of the present invention, and are not intended to limit the present invention. Anyone familiar with the technology may modify or change the above embodiments without violating the spirit and scope of the present invention. Therefore, all equivalent modifications or changes made by a person with ordinary knowledge in the technical field without departing from the spirit and technical ideas disclosed by the present invention should still be covered by the claims of the present invention.
[0081] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each implementation mode may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A CNTs-reinforced asphalt permeable concrete, characterized in that: The invention is composed of the following components in parts by weight: 4-12 parts of modified asphalt, 75-85 parts of coarse aggregate, 6-10 parts of fine aggregate, 4-7 parts of cement, 3-5 parts of mineral powder, 1-1.5 parts of slaked lime and 0.2-0.8 parts of reinforcing material CNTs.
2. The CNTs-enhanced asphalt permeable concrete according to claim 1, characterized in that: The modified asphalt is mixed with base asphalt, a modifier and a composite stabilizer. The mixing amount of the modifier is 4.5% to 5.5%, and the mixing amount of the composite stabilizer is 0.1% to 0.2%.
3. The CNTs-enhanced asphalt permeable concrete according to claim 2, characterized in that: The modifier is prepared by copolymerizing petroleum resin, styrene and modified high-performance polyurethane resin in a mass ratio of 100:7-9:10-14.
4. The CNTs-enhanced asphalt permeable concrete according to claim 2, characterized in that: The composite stabilizer is composed of sulfur powder, polyvinyl alcohol and toluene diisocyanate in a mass ratio of 100:20-30:5-10.
5. The CNTs-enhanced asphalt permeable concrete according to claim 1, characterized in that: The coarse aggregate is a hard stone mixed with basalt, diabase and limestone. The particle size range of the coarse aggregate is 3.0mm to 15.0mm, and the specific grading range is: the pass rate of the sieve hole size of 16mm is 100%, the pass rate of the sieve hole size of 13.2mm is 85% to 87%, the pass rate of the sieve hole size of 9.5mm is 30% to 32%, the pass rate of the sieve hole size of 4.75mm is 5.0% to 6.4%, and the pass rate of the sieve hole size of 2.36mm is 0.5% to 1.0%.
6. The CNTs-enhanced asphalt permeable concrete according to claim 1, characterized in that: The fine aggregate is limestone, and the particle size range of the fine aggregate is 0.075mm-3.0mm. The specific grading range is: the pass rate of the sieve hole size of 4.75mm is 100%, the pass rate of the sieve hole size of 2.36mm is 90%-92%, the pass rate of the sieve hole size of 1.18mm is 64%-66%, the pass rate of the sieve hole size of 0.6mm is 52%-54%, the pass rate of the sieve hole size of 0.3mm is 25%-26%, the pass rate of the sieve hole size of 0.15mm is 18%-18.5%, and the pass rate of the sieve hole size of 0.075mm is 3.2%-3.6%.
7. The CNTs-enhanced asphalt permeable concrete according to claim 1, characterized in that: The cement is ordinary Portland cement, with a 28-day compressive strength of ≥42.5MPa, a 28-day flexural strength of ≥7.0MPa, and a specific surface area of ≥320m 2 / kg.
8. The CNTs-enhanced asphalt permeable concrete according to claim 1, characterized in that: The mineral powder is limestone mineral powder, with a particle size range of ≤0.075mm, a 28-day activity index ≥95%, and a specific surface area ≥420m 2 / kg; the slaked lime is a white powdery matrix with an apparent density of ≥2.2g / cm 3 .
9. The CNTs-enhanced asphalt permeable concrete according to claim 1, characterized in that: The reinforcing material CNTs is a multi-walled hydroxy carbon nanotube with a diameter of 10nm to 20nm, a length of 30μm to 50μm, and a specific surface area of ≥220m 2 / g.
10. A method for preparing CNTs-reinforced asphalt permeable concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Preheat the stirring device to 155℃~165℃, add graded coarse aggregate and fine aggregate into the stirring device, and stir and mix evenly for 100s~150s; S2, heating the modified asphalt to 165° C., adding it to the aggregate treated in step S1, continuing to stir for 180s to 200s, then adding cement, mineral powder and slaked lime, and mixing for 120s to 180s in a stirring manner to obtain an asphalt mixture; S3, adding the reinforcing material CNTs to the asphalt mixture of step S2, heating to 180°C to 200°C, and performing high-speed shear stirring at a speed of 3000r / min to 3200r / min for 60s to 120s to obtain CNTs-reinforced asphalt permeable concrete.
Citation Information
Patent Citations
A permeable high-strength asphalt concrete and its preparation method
CN112897959B